Sex segregation in the workplace : trends, explanations, remedies - Reskin, Barbara F. (National Academy Press, 1984)
How pervasive is sex segregation in the workplace? Does the concentration of women into a few professions reflect their personal preferences, the "tastes" of employers, or sex-role socialization? Will greater enforcement of federal antidiscrimination laws reduce segregation? What are the prospects for the decade ahead? These are among the important policy and research questions raised in this comprehensive volume, of interest to policymakers, researchers, personnel directors, union leaders--anyone concerned about the economic parity of women